Nanoparticles/thermosensitive hydrogel reinforced with chitin whiskers as a wound dressing for treating chronic wounds. Issue 17 (12th April 2017) - Xia, Guixue; Liu, Ya; Tian, Meiping; Gao, Ping; Bao, Zixian; Bai, Xiaoyu; Yu, Xiaoping; Lang, Xuqian; Hu, Shihao; Chen, Xiguang
Abstract : Nanoparticles/thermosensitive hydrogel reinforced with chitin whiskers as a wound dressing for treating chronic wounds. Abstract : Cutaneous chronic wounds are characterized by impaired wound healing which may lead to infection and even amputation. To surmount this problem, we developed a chitin whisker (CW)/carboxymethyl chitosan nanoparticles (CMCS NPs)/thermosensitive hydroxybutyl chitosan (HBC) composite hydrogel (CW/NPs/HBC-HG) as a wound dressing for treating chronic wounds. Upon introduction of CWs, the composite hydrogel exhibited a significant decrease in gelation temperature and enhanced mechanical properties. The storage modulus ( G ′) of the CW/NPs/HBC-HG was 3.6 times that of the NPs/HBC-HG at 37 °C and the ex vivo rat skin test also showed that the mechanical properties were significantly improved. Linezolid, a wide-spectrum antibiotic, was dissolved directly in the water phase of the composite hydrogel, and the antibacterial activity of the composite hydrogel against Escherichia coli and Staphylococcus aureus was up to 99% until 7 days. When recombinant human epidermal growth factor (rhEGF) was encapsulated into the NPs, the CW/NPs/HBC-HG offered prolonged cell proliferation activity up to 5 days. More importantly, the in vivo chronic wound healing model evaluation in diabetic rats revealed that the CW/NPs/HBC-HG dressing promoted wound healing and accelerated reepithelialization, collagen deposition and angiogenesis. These findings demonstrated that CW/NPs/HBC-HG is a promising dressing for chronic wounds.